Handbook of research on smart territories and entrepreneurial ecosystems for social innovation and sustainable growth - Palma-Ruiz, Jesús Manuel 1978-; Sáiz Álvarez, José Manuel; Herrero-Crespo, Ángel (IGI Global, 2020)
""This book explores smart specialization strategy as an exportable model for improving competitiveness in different environments"--Provided by publisher"--
Keywords: Sustainable development; Regional planning